Stomach dose-volume parameters and clinical factors predict acute toxicity in pancreatic cancer chemoradiotherapy - Holyoake, D; Partridge, M; Hurt, C; Mukherjee, S; Hawkins, M (Elsevier, 2017)
Gastrointestinal (GI) toxicity impedes dose escalation and likelihood of cure in chemoradiotherapy (CRT) for hepatobiliary malignancies. The risk of toxicity can depend on clinical and radiotherapy (RT) dose-volume metrics. We aimed to identify predictive factors using data from two prospective phase-II clinical trials of locally-advanced pancreatic cancer (LAPC).